2019
DOI: 10.1007/s12192-019-01013-y
|View full text |Cite
|
Sign up to set email alerts
|

High basal heat-shock protein expression in bats confers resistance to cellular heat/oxidative stress

Abstract: Bats, unique among mammals with powered flight, have many species with the longest size-proportionate lifespan of all mammals. Evolutionary adaptations would have been required to survive the elevated body temperatures during flight. Heat shock protein (HSP), highly conserved master regulators of cell stress, expression was examined across tissues and various cell lines in bats. Basal expression level of major HSPs (HSP70 and HSP90) is significantly higher in two different bat species compared to other mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…This could hypothetically lead to the observed G-U and C-A mutation asymmetry. Bats have evolved increased resistance to oxidative stress (Chionh et al, 2019), which could explain why the excess of G-U substitutions is not observed between SARS-CoV-2 and bat coronavirus RaTG13. It is unclear, however, why SARS-CoV-2 is different from SARS-CoV in this regard.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could hypothetically lead to the observed G-U and C-A mutation asymmetry. Bats have evolved increased resistance to oxidative stress (Chionh et al, 2019), which could explain why the excess of G-U substitutions is not observed between SARS-CoV-2 and bat coronavirus RaTG13. It is unclear, however, why SARS-CoV-2 is different from SARS-CoV in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…In either scenario, SARS-CoV-2 would be exposed to both a novel evolutionary landscape that affects the fitness of its genetic variants and novel cellular conditions that could affect its mutation rates directly. For example, it is known, that bats have evolved a number of adaptations including superior resistance to oxidative stress (Chionh et al, 2019) that allow them to harbor multiple viruses without getting the corresponding diseases (Schountz et al, 2017). In light of this, we decided to investigate if the relative mutation frequencies in SARS-CoV-2 changed after its transmission to human hosts.…”
Section: Introductionmentioning
confidence: 99%
“…HSP70, in contrast, is a fundamental anti-inflammatory chaperone of the HSR that may inhibit cytokine storm induced by SARS viruses through binding/degrading p65 subunit of NF-κB [ 79 ], which is needed for a complete inflammatory response and, eventually, a cytokine storm. On the other hand, Chionh and colleagues [ 80 ] have shown that a huge basal expression of HSPs in bats (discussed in detail below) is associated with cell survival to prolonged heat treatment and defense against oxidative stress. From the other point of view, bats are capable of mounting a perpetually activated IFN response [ 81 ] without suffering from any hyperinflammation-induced cytokine storm.…”
Section: Heat Shock Response (Hsr) Fever and The Physiological Resolmentioning
confidence: 99%
“…This could hypothetically lead to the observed G to U and C to A mutation asymmetry. Bats have evolved increased resistance to oxidative stress [8], which could explain why the excess of G to U substitutions is not observed between SARS-CoV-2 and bat coronavirus RaTG13. It is unclear, however, why SARS-CoV-2 is different from SARS-CoV in this regard.…”
Section: Resultsmentioning
confidence: 99%